Understanding the Role of Nitronate Monooxygenases in Virulence of the Human Fungal Pathogen Aspergillus fumigatus - Phuong Tuyen Nguyen; Theresa Wacker; Alistair J. P. Brown; Alessandra da Silva Dantas; Elena Shekhova (Journal of Fungi, 2022)
Aspergillus fumigatus is the leading cause of the fungal invasive disease called aspergillosis, which is associated with a high mortality rate that can reach 50% in some groups of immunocompromised individuals. The increasing prevalence of azole-resistant A. fumigatus isolates, both in clinical settings and the environment, highlights the importance of discovering new fungal virulence factors that can potentially become targets for novel antifungals. Nitronate monooxygenases (Nmos) represent potential targets for antifungal compounds as no orthologs of those enzymes are present in humans. Nmos catalyse the denitrification of nitroalkanes, thereby detoxifying these mediators of nitro-oxidative stress, and therefore we tested whether Nmos provide protection for A. fumigatus against host-imposed stresses at sites of infection. The results of inhibition zone assays indicated that Nmo2 and Nmo5 are not essential for the oxidative stress resistance of A. fumigatus in vitro. In addition, the resazurin-based metabolic activity assay revealed that the growth of mutants lacking the nmo2 or nmo5 genes was only slightly reduced in the presence of 0.05 mM peroxynitrite. Nevertheless, both Nmo2 and Nmo5 were shown to contribute to defense against murine bone marrow-derived macrophages, and this was no longer observed when NADPH oxidase, the main generator of reactive oxygen species during infection, was inhibited in macrophages. Furthermore, we revealed that Nnmos promote the virulence of the fungus in the Galleria mellonella model of infection. Both nmo2 and nmo5 knock-out strains were less virulent than the wild-type control as recorded 72 h post-infection. Our results indicate that Nmos play a role in the virulence of A. fumigatus.